4-Carboxyphenyl isothiocyanate as a Lewis base additive for efficient and stable perovskite solar cells - Fu, Shuai; Ma, Yuhui; Zhang, Zhiyuan; Xu, Yao; Zhang, Heyi; Xiao, Zihan; Zhang, Sihao; Xia, Ruidong (Synthetic Metals, 2023)
A high-quality perovskite film is of great significance for efficient and stable perovskite solar cells (PSCs). The use of additives to improve the crystallinity and morphology of perovskite films is an effective way to improve the performance of PSC devices. In this work, 4-carboxyphenyl isothiocyanate (CPIC) was used as an additive in perovskite films to improve the quality of the films. The results of FT-IR showed that the SCN- and -COOH groups with Lewis base in CPIC can coordinate with unpaired Pb2+ on the perovskite films to form Lewis acid-base adducts. The addition of CPIC can effectively improve the crystallinity and grain size of the perovskite films. The results showed that the short circuit current density (JSC) and fill factor (FF) of PSC devices increase significantly with the improvement of film quality, when the concentration of CPIC is 0.5 mg mL−1. These made the efficiency of the devices increase from 16.16 % to 18.19 %. Meanwhile, the introduction of the benzene ring in CPIC can improve the stability of the PSC devices. After aging at room temperature and 50 % humidity for 30 days, the device added with CPIC retained 61.9 % of the initial PCE. This work proves that using CPIC as an additive is an effective method to achieve efficient and stable PSCs.
CRIS-Team Scopus Importer:2023-01-13
Keywords: Crystallinity; Film morphology; Inverted perovskite solar cells; Lewis base additives

Understanding the Microstructure Formation of Polymer Films by Spontaneous Solution Spreading Coating with a High-Throughput Engineering Platform - Wang, Rong; Lüer, Larry; Langner, Stefan; Heumüller, Thomas; Forberich, Karen; Zhang, Heyi; Hauch, Jens; Li, Ning; Brabec, Christoph (Chemsuschem, 2021)
An important step of the great achievement of organic solar cells in power conversion efficiency is the development of low-band gap polymer donors, PBDB−T derivatives, which present interesting aggregation effects dominating the device performance. The aggregation of polymers can be manipulated by a series of variables from a materials design and processing conditions perspective; however, optimization of film quality is a time- and energy-consuming work. Here, we introduce a robot-based high-throughput platform (HTP) that is offering automated film preparation and optical spectroscopy thin-film characterization in combination with an analysis algorithm. PM6 films are prepared by the so-called spontaneous film spreading (SFS) process, where a polymer solution is coated on a water surface. Automated acquisition of UV/Vis and photoluminescence (PL) spectra and automated extraction of morphological features is coupled to Gaussian Process Regression to exploit available experimental evidence for morphology optimization but also for hypothesis formulation and testing with respect to the underlying physical principles. The integrated spectral modeling workflow yields quantitative microstructure information by distinguishing amorphous from ordered phases and assesses the extension of amorphous versus the ordered domains. This research provides an easy to use methodology to analyze the exciton coherence length in conjugated semiconductors and will allow to optimize exciton splitting in thin film organic semiconductor layers as a function of processing.
CRIS-Team Scopus Importer:2021-07-16
Keywords: Gaussian process regression; high-throughput engineering; microstructure morphology; organic photovoltaics; spontaneous film spreading